A critical view of long-term AVHRR aerosol data record in China: Retrieval frequency and heavy pollution. (15th February 2020) - Tao, Minghui; Li, Rong; Wang, Lili; Lan, Feng; Wang, Zifeng; Tao, Jinhua; Che, Huizheng; Wang, Lunche; Chen, Liangfu
Abstract: The recent AVHRR aerosol products expended from MODIS Deep Blue (DB) algorithm provide an unprecedented long-term data record over land that dates back to 1980s. Unlike previous studies focused on performance of AVHRR retrievals, here we present a critical view into the influence of retrieval frequency on consistency of AVHRR Aerosol Optical Depth (AOD) with other satellite DB products, and application potential in characterizing the dramatic aerosol loading in China. Despite the good consistency of collocated AVHRR, SeaWiFS, and MODIS DB AOD, their different retrieval frequency leads to distinct distribution of annual or seasonal AOD. In particular, the over-strict cloud screening of AVHRR with fewer bands tends to filter out high-AOD and clean bright surface, with the overall AOD frequency only half of MODIS's. Retrieval frequency and selection criterion of AOD quality can determine representativity and consistency of conventional averaged satellite AOD, uncertainties of which should be considered according to specific application purpose. The time series variation of AVHRR AOD shows that early 1990s is a key time point when frequent haze pollution appears and increases in eastern China. By contrast, aerosol loading in 1995–1999 has reached similar level as in 2000s with notable hotspot of high-AOD ( 0.8–0.9) and slight changes. Our results shows that full record of AVHRR aerosol products with corresponding improvement can greatly renew the understanding of aerosols in China. Highlights: Retrieval frequency has significant influence on consistency in multiple satellite Deep Blue aerosol products. AVHRR Deep Blue retrievals tends to miss high-AOD and clean bright surface due to over-strict cloud screening. Early 1990s is a key time point that frequent haze pollution appears and increases in eastern China.